Synergistic antiulcer activity of methanolic extract of a mixture of Cinnamon cassia Bark and Annona squamosa twigs in indomethacin-induced ulcer - Kasturi Viswanathsetty Veerabhadrappa; Pasam Devika`````````````; Dharmavaram Deepti; Gaurav Gupta; Gorantla Narayana; Bhupalam Pradeep Kumar; Yiragam Reddy Padmanabha Reddy (Asian Pacific Journal of Health Sciences, 2018)
Background: Cinnamon cassia bark and Annona squamosa twigs have been individually described to possess antiulcer activity. In an effort to develop a pharmaceutical product with gastroprotective potential, the synergistic antiulcer effect of methanolic extract of a mixture of C. cassia bark and A. squamosa twigs at 50:50 ratios was assessed in experimental animals. Aim: Antiulcer activity of methanolic extracts of C. cassia (MECC) bark and A. squamosa twigs was studied in rats, in which gastric ulcers were induced by indomethacin (20 mg/kg, orally) followed by pylorus ligation method. Method: The methanolic extract of A. squamosa twigs (MEAS) (100 mg/kg); MECC bark (100 mg/kg); mixture of a (MEAS) twigs and MECC bark (50 mg/kg:50 mg/kg, respectively) was administered orally to the rats for 6 consecutive days followed by pylorus ligations of a stomach on the 7th day of experiment. After 4 h of ligation, the animals were subjected for evaluation of ulcer index and gastric acid content. Result: The reduction of ulcer index and gastric acid content in mixture of a MEAS and MECC-treated animals was seen to be statistically significant with respect to control group of rats. Conclusion: The mixture of a MEAS and MECC exhibited better ulcer protection effect as compared to individual effect of MEAS and MECC. Misoprostol was used as a standard drug for ulcer protection.